An introduction to radical participatory design: decolonising particip atory design processes - Udoewa, Victor (Design Science, 2022)
Outside of community-led design projects, most participatory design pr ocesses initiated by a company or organisation maintain or even streng then power imbalances between the design organisation and the communit y on whose purported behalf they are designing, further increasing the absencing experience. Radical participatory design (RPD) is a radical ly relational answer to the coloniality inherent in participatory desi gn where the community members’ disappointment is greater due to the g reater expectations and presencing potential of a ‘participatory desig n’ process. We introduce the term RPD to show how research and design processes can be truly participatory to the root or core. Instead of t reating participatory design as a method, a way of conducting a method , or a methodology, we introduce RPD as a meta-methodology, a way of d oing any methodology. We explicitly describe what participation means and compare and contrast design processes based on the amount of parti cipation, creating a typology of participation. We introduce ‘designer as community member’, ‘community member as designer,’ and ‘community member as facilitator’ models and provide characteristics for the meta -methodology of RPD.
Keywords: critical design; decolonising design; design justice; participatory design; participatory research; research justice